Analisis Rasch Model: Mengukur Kualitas Butir Soal Tes Tashrif Lughawi - Hayati, Salma; Hidayanti, Sri Wahyuni; Rizki, Aulia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to test the quality of the items of the Tashrif Lughawi using Rasch Model analysis. This study measured test items with item polarity tests, item and respondent mapping, individual and item reliability. This instrument contains 20 objective items test. This instrument test was tested on 51 students of the Madrasah Tsanawiyah level. The research data was analyzed using the Winsteps program for Rasch Model analysis. The result of Rasch's analysis based on item polarity shows that all test items are positive Point Measure Correlation (PMC) value. This result means that there is no conflict between the item and the constructed being measured. The results of the Mean Square Value show that 18 items have a value less than 1.5 which means that the resulting measurement is productive. 2 items -soal_10 (1.83) and soal_4 (1.64)- have a value greater than 1.5, so it is necessary to review this item for use decision-making. The results of the reliability analysis showed that the reliability index of the item was 0.91 and the reliability index of the respondents was 0.80. The results of this study show that the Tashrif Lughawi test instrument has high validity and reliability so that it can be used as a tool to measure the ability of Tashrif Lughawi students at the Madrasah Tsanawiyah level.